2017
DOI: 10.1002/phar.1974
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a Driver in Advancing Precision Medicine in Sepsis

Abstract: Objective The objective of this review is to explain the science of metabolomics—a science of systems biology that measures and studies endogenous small molecules (metabolites) that are present in a single biological sample—and its application to the diagnosis and treatment of sepsis. In addition, we discuss how discovery through metabolomics can contribute to the development of precision medicine targets for this complex disease state and the potential avenues for those new discoveries to be applied in the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 64 publications
(146 reference statements)
1
50
0
1
Order By: Relevance
“…On the other hand, metabolomics has been characterized as a driver for personalized medicine in sepsis [99]. Taken together with the fact that sepsis, as mentioned above, is a global health concern, this underlines the significance of metabolomics for public health.…”
Section: Impact On Public Healthmentioning
confidence: 99%
“…On the other hand, metabolomics has been characterized as a driver for personalized medicine in sepsis [99]. Taken together with the fact that sepsis, as mentioned above, is a global health concern, this underlines the significance of metabolomics for public health.…”
Section: Impact On Public Healthmentioning
confidence: 99%
“…Rather, we reviewed the literature surrounding the biological relevance of the metabolites in the context of sepsis. A literature review by Eckerle et al, reported statistically significant metabolites that were found to be related to three pathways, namely, energy metabolism, mitochondrial dysfunction, and platelet activation and/or aggregation (Table 4) [17].…”
Section: Multiple Linear Regression Models Analysismentioning
confidence: 99%
“…Critically, platelet mitochondrial respiration, or mitochondrial oxygen consumption rates (mOCR), has been found to be associated with sepsis clinical parameters, such as severity of illness, organ failure, and mortality [11,12]. Metabolomics, the measurement of small molecules (<1500 Daltons), or metabolites, in a single biological sample, is an another effective approach for the study of the impact of sepsis on mitochondrial function [17]. Recently, Chacko et al, showed that the platelet metabolome in healthy subjects is functionally integrated with platelet mOCR [18].…”
Section: Introductionmentioning
confidence: 99%
“…SIRS can be too sensitive and not specific and qSOFA has been found to be specific but poorly sensitive [34,35]. Metabolite biomarkers such as lactate and creatinine have been proven to have the potential to assist the diagnosis of sepsis, and ongoing work seeks panels of metabolites whose abundance changes provide increased sensitivity in diagnosis [36][37][38]. Therefore, methods to detect multiple metabolite biomarkers simultaneously in a short time will be necessary for the rapid diagnosis of sepsis, reducing the risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the capability of the sensor platform, glucose and lactate were chosen as the analytes since they have been shown to have relevance as indicators in early diagnosis of sepsis. [37,[39][40][41][42] Three microfluidic channels were fabricated on a single paper strip and each channel subsequently printed with enzymes for detecting glucose and lactate. The third channel was used as a control in this study.…”
Section: Introductionmentioning
confidence: 99%